Response Time Threshold for Predicting Outcomes of Patients with Out-of-Hospital Cardiac Arrest. (11th February 2021) - Huang, Ling Hsuan; Ho, Yu-Ni; Tsai, Ming-Ta; Wu, Wei-Ting; Cheng, Fu-Jen
Abstract : Ambulance response time is a prognostic factor for out-of-hospital cardiac arrest (OHCA), but the impact of ambulance response time under different situations remains unclear. We evaluated the threshold of ambulance response time for predicting survival to hospital discharge for patients with OHCA. A retrospective observational analysis was conducted using the emergency medical service (EMS) database (January 2015 to December 2019). Prehospital factors, underlying diseases, and OHCA outcomes were assessed. Receiver operating characteristic (ROC) curve analysis with Youden Index was performed to calculate optimal cut-off values for ambulance response time that predicted survival to hospital discharge. In all, 6742 cases of adult OHCA were analyzed. After adjustment for confounding factors, age (odds ratio [OR] = 0.983, 95% confidence interval [CI]: 0.975–0.992, p < 0.001 ), witness (OR = 3.022, 95% CI: 2.014–4.534, p < 0.001 ), public location (OR = 2.797, 95% CI: 2.062–3.793, p < 0.001 ), bystander cardiopulmonary resuscitation (CPR, OR = 1.363, 95% CI: 1.009–1.841, p = 0.044 ), EMT-paramedic response (EMT-P, OR = 1.713, 95% CI: 1.282–2.290, p < 0.001 ), and prehospital defibrillation using an automated external defibrillator ([AED] OR = 3.984, 95% CI: 2.920–5.435, p < 0.001 ) were statistically and significantly associated with survival to hospital discharge. The cut-off value was 6.2 min. If the location of OHCA was a public place or bystander CPR was provided, the threshold was prolonged to 7.2 min and 6.3 min, respectively. In the absence of a witness, EMT-P, or AED, the threshold was reduced to 4.2, 5, and 5 min, respectively. The adjusted OR of EMS response time for survival to hospital discharge was 1.217 (per minute shorter, CI: 1.140–1299, p < 0.001 ) and 1.992 (<6.2 min, 95% CI: 1.496–2.653, p < 0.001 ). The optimal response time threshold for survival to hospital discharge was 6.2 min. In the case of OHCA in public areas or with bystander CPR, the threshold was prolonged, and without witness, the optimal response time threshold was shortened.